2009
DOI: 10.1161/circulationaha.109.851014
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Percutaneous Device Implantation for Closure of Patent Foramen Ovale on Valve Insufficiencies

Abstract: Background-In patients with percutaneous device implantation for closure of patent foramen ovale (PFO), a 10% incidence of new or worsened aortic regurgitation within 12 months has been reported with echocardiography. Cardiac magnetic resonance imaging is a powerful noninvasive tool to quantify volume and fraction of valve insufficiencies. We studied the acute and long-term impact of percutaneous device implantation for PFO closure on valve insufficiencies in cardiac magnetic resonance imaging. Methods and Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…In another study, Wöhrle et al used cardiac magnetic resonance imaging (MRI) to examine the impact of PFO device closure on AR . They performed sequential MRI on 102 patients before and 12‐months following device closure, and concluded that percutaneous device closure of PFO had no impact on valve competency, including AR.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Wöhrle et al used cardiac magnetic resonance imaging (MRI) to examine the impact of PFO device closure on AR . They performed sequential MRI on 102 patients before and 12‐months following device closure, and concluded that percutaneous device closure of PFO had no impact on valve competency, including AR.…”
Section: Discussionmentioning
confidence: 99%
“…The ASO abolished the former left‐to‐right shunt at the atrial level, thus unloading the enlarged right atrium and right ventricle in this patient group. The median time interval between defect closure and MR study was 23 days (1–120). The inner diameters of the occluders ranged from 14 to 26 mm.…”
Section: Methodsmentioning
confidence: 99%
“…The bulky profile of the ASO and the need of atrial stretch and deformation raise concerns and led to the development of lower‐profile devices (5). A 10% rate of newly developed or worsened aortic regurgitation was observed after implantation of Amplatzer PFO occluders (6).…”
mentioning
confidence: 99%
“…All data were acquired utilizing a dedicated 5-element cardiac phased-array coil. To determine left and right ventricular function, a retrospective ECG-gated segmented k-space balanced turbo field-echo sequence (steady-state free-precession [SSFP]) was used in short-and long-axis views along the true heart axis (11). Depending on the required field of view, the spatial resolution was Wöhrle et al Myocardial Scar and Cryptogenic Stroke between 1.7 ϫ 1.8 mm and 2.3 ϫ 1.8 mm in-plane.…”
Section: E T H O D Smentioning
confidence: 99%